Bacterial Contamination of Mussels at Mahe Estuary, Malabar Coast - P.S., Gore; O., Raveendran; T.S.G., Iyer; P.R.G., Varma; V.N., Sankaranarayanan (Fishery Technology, 2025)
Mussel samples from the mussel bed and near-by market, beach sand, sediment and water from the Mahe estuary were analysed for the bacterial quality. Indicator bacteria such as Escherichia coli and faecal streptococci were isolated from water, sediment and both mussel samples especially during monsoon and postmonsoon months. Pathogens like Salmonella and Vibrio cholerae non 01 were isolated from the mussel samples. The sewage and land drainage of the region contribute to the contamination of the environment.